Cover, Volume 41, Issue 10. Issue 10 (28th September 2020) - Kaur, Simranpreet; Van Bergen, Nicole J.; Verhey, Kristen J.; Nowell, Cameron J.; Budaitis, Breane; Yue, Yang; Ellaway, Carolyn; Brunetti‐Pierri, Nicola; Cappuccio, Gerarda; Bruno, Irene; Boyle, Lia; Nigro, Vincenzo; et al.
Abstract : The cover image is based on the Research Article Expansion of the phenotypic spectrum of de novo missense variants in kinesin family member 1A (KIF1A) by Simranpreet Kaur et al., https://doi.org/10.1002/humu.24079 .